PKM Pemanfaatan Fanspage dan Ads Facebook sebagai Strategi Pemasaran Produk pada Komunitas Online Shop Situbondo - Fathorazi Nur Fajri; Siti Aisyah; Suhdil Ibadi; Abdur Rohman Sholeh; Muhammad Roziqin; Agung Maulana (Universitas Nurul Jadid, 2021)
During the covid 19 pandemic, all activities involving and causing crowds are prohibited in order to prevent the transmission of the covid 19 virus. Buying and selling business activities were also affected where before the pandemic was done in the traditional market when it has changed to online group groups on Facebook or e-commerce. Fanspages or Pages are used by businesses, brands, organizations, and public figures to share their stories and connect with people. Like profiles, Pages can be customized for stories, events, and more. People who like or follow a Page will get updates in News Feed. The sheer number of similar things makes competition increasingly difficult to get buyers. therefore it takes sharing knowledge or knowledge in order to get a good and targeted marketing strategy. in addition, it requires an introduction related to tools that can facilitate market activities. so that with good marketing is expected to increase revenue.